Feeding and working strategies for oxen used for draft purposes in semi-arid West Africa - Fall, Abdou; Pearson, R.A.; Lawrence, P.R.; Fernández Rivera, S. (1997)
This study was conducted to determine the energy expenditure of draft oxen working on sandy soils, performing common agricultural tasks, so that energy requirements could be determined; to establish the relationships between work and intake and digestibility of roughages by draft oxen; to investigate the effect of body condition before work and liveweight losses during work on work performance, and to investigate the implications of heat stress on draft oxen in semi-arid areas. This information will allow informed decisions to be made on the feeding and management of draft animals in semi-arid areas. Four experiments were conducted. Experiment 1 investigated the energy costs of walking on soils of different consistencies and the efficiencies of doing work. Experiment 2 and 3 were designed to establish the effect of work on intake, digestibility and rate of passage of feeds (millet stover) in the digestive tract. Experiment 4 looked at the effect of body condition before work and weight losses during work on work performance. The effect of heat stress was also investigated in experiment 2, 3 and 4. This report gives details of these experiments, the results obtained and, based on these, the recommendations made regarding feeding and working strategies for draft oxen in semi-arid areas.